Hubungan Self Efficacy dengan Self Care Managament Pasien Hipertensi - Reski Awalia; Mikawati; Hidayati Ismail (Politeknik Baubau, 2024)
Introduction : Hypertension is a noncommunicable disease and as the leading cause of death which is known as the silent killer due to its prevelance without any symptoms. Therefore, a patient with high blood pressure needs to control their condition by doing efforts such as self-care management and self-efficacy. Objective : The aim of the research is to find out the correlation of self-efficacy and self-care management of the patients with hypertension in the work region of Puskesmas Samata, Gowa regency Reearch Method : The research is quantitative study that employs the observational analytics of Cross-sectional study. As many as 66 respondents were included as the samples by using non probability sampling technique with the approach of purposive sampling. The instruments were the quistionnaires of self-efficacy to manage hypertension (SEMH) and Hypertension Self- Management Behavior Questionnaire (HSMBQ). The data were analyzed by Chi-Square. Result : There were 43 (65.2%) of respondents who had low self-efficacy, and 45 (68.2%) of respondents who owned lack self-care management. The test result of chi-square showed the significance correlation between self-efficacy and self-care management of the hypertension patients in the work region of Puskesmas Samata, Gowa regency by confirming the p value = Conclusion and suggestion : The higher the self-efficacy, the better the self-care management of the hypertension patients, and vice versa. The patients with hypertension should improve their self- efficacy to achieve the behavior of good self-care management.